Faktor-Faktor yang Mempengaruhi Tingkat Kepuasan Pasien Rawat Inap di Rumah Sakit Umum Daerah Provinsi Sulawesi Tenggara - Elwindra Elwindra; Alfatihah Reno Maulani (STIKes Persada Husada Indonesia, 2014)
Patient satisfaction is the most important aspect of operational level in hospital services. From consumer’s point of view, patient satisfaction level is one of the major factors that have a big impact to hospital achievement to increase number of visiting patient. The objective of the study is to identify influential factors of patient satisfaction level at inpatient ward of South-East Sulawesi Province General Hospital in terms of characteristic of patient through the Service Quality – Servqual Method by measuring the gap between perceived and expected service on 5 patient satisfaction dimensions, which are: Tangibles, Reliability, Responsiveness, Assurance, and Empathy.The measurement of satisfaction level was conducted to 108 respondents through selfadministered questionnaire with cross sectional design. The primary data were analysed using Univariate, Bivariate and Multivariate Analysis, and appropriateness level between perceived and expected service at inpatient ward through Importance Performance Analysis.The result of this study showed that the characteristic of patient that having significant relationship and dominant influence with patient satisfaction level was the distance from patient residence to the hospital. Patient with extended distance from the hospital was more satisfied 6.070 times than nearby patient. The patient satisfaction level is 83.27%, with description of every dimension: Assurance (86.53%), Empathy (85.41%), Responsiveness (83.38%), Reliability (81.89%), and Tangibles (79.13%). Importance-Performance Analysis has found 5 factors as main priorities (quadrant A) which are the weakness factors at inpatient ward of South-East Sulawesi Province General Hospital. In general, the main priorities are Tangibles and Reliability dimension.